PERANCANGAN SEKOLAH RAMAH ANAK PADA SDN PONDOK CINA 1 DENGAN PENDEKATAN FLEKSIBILITAS RUANG DI KOTA DEPOK - Alvia Salsadiva Permana; Nia Suryani; Ryan Hidayat (Universitas Indraprasta PGRI, 2022)
Depok is participates in efforts to fulfill children's rights and protect children in schools through the Child Friendly School program in the Child Friendly City policy. This study aims to design a Child Friendly School in accordance with Child Friendly School standards by the Ministry of Women's Empowerment and Child Protection at SDN Pondok Cina 1, Depok. The spatial flexibility approach was chosen as a solution to the problem of limited land that occurs at the site through three concepts , namely versatility , convertibility , and expansibility . These three concepts of spatial flexibility are applied to classrooms, also the concept of convertibility is applied to student toilets. Versatility is realized with classrooms that could be transform into meeting room, exhibition room also hall. Convertibility is realized by arranging classroom furniture that adapts to learning methods also ergonomic designs on classroom furniture and student’s toilets that suitable with the body size of elementary school student. Expansibility is realized by the expansion of classrooms that blend with the corridor. Besides to design the elementary school that meet the Child Friendly School standards, the result of this research hope could be considered in advancing the quality of public elementary school education in Depok.